Legal Cases Regarding Online Loans Relating to Violations of Contract Agreements and Debtor Data Protection - Cokorda Istri Ratih Laksmi Dewi; Kadek Januarsa Adi Sudharma (JURNAL AKTA, 2025)
The expansion of online lending services (peer-to-peer lending) in Indonesia has facilitated easier access to credit but simultaneously introduces legal risks related to contract breaches and the protection of borrowers’ personal data. This study adopts a literature review approach to examine actual cases and the relevant legal framework, including the Consumer Protection Law, the Electronic Information and Transactions Law, and the Personal Data Protection Law. The analysis reveals that, despite the existing regulations, online lending practices remain susceptible to issues such as excessive interest rates, unauthorized dissemination of personal data, and aggressive debt collection practices. Ensuring effective legal protection necessitates comprehensive consumer education, stringent regulatory oversight, and rigorous enforcement of sanctions. This study contributes to understanding the legal challenges within the fintech sector and highlights the critical importance of safeguarding consumers to maintain a fair and secure online lending environment.